New Perspectives of Underlying Cardiomyopathy in Pediatric SMA Patients—An Age Matched Control Study - Georgiana Nicolae; Andrei Capitanescu; Madalina Cristina Leanca; Elena Neagu; Daniela Vasile; Cristina Filip; Eliza Cinteza; Amelia Aria; Bianka Maria Pavlov; Gabriela Uscoiu; Cristiana Ioana Raita; Andrada Mirea (Life, 2025)
Spinal muscular atrophy (SMA) is a genetic neuromuscular disorder primarily affecting motor neurons. Emerging evidence suggests it also involves multiple organs, including potential cardiac manifestations. This study aimed to evaluate cardiac abnormalities in pediatric SMA patients compared to age-matched healthy controls, providing insight into underlying cardiomyopathy in this population. A total of 126 children were included in the study, with 63 SMA patients and 63 age-matched controls. We conducted clinical examinations, standard electrocardiography (ECG), and cardiac ultrasound (CUS) in all patients. Electrocardiographic analysis revealed a higher prevalence of sinus tachycardia in the SMA group and significantly deeper Q waves, indicating possible myocardial involvement. Echocardiographic findings demonstrated a significant reduction in left ventricular mass and left ventricular mass index in SMA patients compared to controls, despite normal systolic function. Statistical analysis confirmed that SMA diagnosis was an independent predictor of reduced myocardial mass, suggesting a distinct cardiac phenotype in SMA patients. This study provides new evidence of subclinical cardiac involvement in SMA, characterized by reduced myocardial mass, altered electrocardiographic parameters, and increased sinus tachycardia. These findings suggest a previously unrecognized form of cardiomyopathy in SMA that differs from cardiac manifestations typically seen in other neuromuscular disorders.